Agonist-specific Gating of NMDA Receptors - Kussius, Cassandra L. (2010)
The mechanism by which ligand binding at extracellular receptor domains gates a transmembrane ion-conducting pore is insufficiently understood. Examining a channel’s activation reaction in the presence of agonists with distinct efficacies may inform this issue and may help identify agonist-dependent transitions. We have recently applied this approach to NMDA receptors composed of GluN1 and GluN2A subunits. Based on our results with several subunit-specific partial agonists we concluded that agonist effects were distributed over several of the multiple transitions that make up NMDA receptor gating and that these changes were subunit independent. Here we examine an additional GluN2A partial agonist, 4-fluoro-D, L-glutamic acid, and we summarize the observed kinetic changes of all nine partial agonists investigated. These results support the premise that regardless of the subunit-type to which they bind, agonists influence multiple equilibria within the NMDA receptor reaction and may stabilize a slightly different family of conformers.